CTX-M-27- and CTX-M-14-producing, ciprofloxacin-resistant Escherichia coli of the H30 subclonal group within ST131 drive a Japanese regional ESBL epidemic. (16th February 2015) - Matsumura, Yasufumi; Johnson, James R.; Yamamoto, Masaki; Nagao, Miki; Tanaka, Michio; Takakura, Shunji; Ichiyama, Satoshi; ,; Matsumura, Yasufumi; Yamamoto, Masaki; Nagao, Miki; Takakura, Shunji; et al.
Abstract: Objectives: The global increase in ESBL-producing Escherichia coli is associated with the ST131 clonal group, especially its CTX-M-15-producing H 30Rx subset. To understand the rapid spread of ESBL-producing E. coli in Japan, we investigated the molecular epidemiology and ESBL-associated genetic environments of Japanese ST131 isolates. Methods: Between 2001 and 2012, 1079 ESBL-producing E. coli isolates were collected at 10 Japanese acute-care hospitals. ESBL types, ST131 status, fimH allele, H 30Rx-defining sequences and ESBL-associated genetic environments were defined using PCR and sequencing. Subclonal groups were defined based on fimH allele and H 30Rx status. Results: Overall, 461 (43%) of the 1079 ESBL-producing E. coli isolates represented ST131. According to fimH -based subclonal typing, the ST131 isolates included 398 fimH allele 30 ( H 30) isolates, 49 H 41 isolates, 10 H 22 isolates and 4 other fimH -type isolates. The 398 H 30 isolates included 396 ciprofloxacin-resistant H 30R isolates, of which 64 (16%) represented the H 30Rx subset. Between 2001 and 2007, the CTX-M-14-producing H 30R subgroup predominated, accounting for 46% of ST131 isolates, whereas the CTX-M-27-producing H 30R and CTX-M-15-producing H 30Rx subgroups were rarely detected. In contrast, from 2008 onward the latter two subgroups rose to dominance, accounting for 45% and 24% of ST131 isolates, respectively, versus only 15% for the (formerly dominant) CTX-M-14-producing H 30R subgroup. The emergent CTX-M-27- H 30R subgroup frequently had an IS 26 -ΔIS Ecp1-bla CTX-M-27 -ΔIS 903D -IS 26 -like structure, whereas the older CTX-M-14- H 30R subgroup frequently had an IS Ecp1-bla CTX-M-14 -IS 903D -like structure. Conclusions: This Japanese regional ESBL-producing E. coli epidemic is closely associated with newly identified CTX-M-27- and CTX-M-14-producing ST131 H 30R subclonal groups and with mobile elements IS 26, IS Ecp1 and IS 903D .